2015
DOI: 10.1590/s0034-8910.2015049005783
|View full text |Cite
|
Sign up to set email alerts
|

Profile of women who carried out smoking cessation treatment: a systematic review

Abstract: OBJECTIVE Analyze the profile of women, in health services, who carry out treatment for smoking cessation.METHODS Systematic review that used the following sources of information: Cummulative Index to Nursing and Allied Health Literature (CINAHL), PubMed, Biblioteca Virtual em Saúde (BVS), Scopus and Web of Science. We included quantitative studies that addressed the characterization of women, in health services, who carried out treatment for smoking cessation, resulting in 12 articles for analysis. The assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
5
0
2
Order By: Relevance
“…Another contributing factor to closing the gap in smoking rates between women and men in the < 55-year age group is the probable greater difficulty experienced by women in quitting smoking. 18 - 20 This is probably related both to physical factors, such as the relationship between nicotine and female hormones, and to emotional factors associated with mood and affect. In addition, earlier age at smoking initiation and longer-term tobacco consumption translate into greater difficulty in quitting smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Another contributing factor to closing the gap in smoking rates between women and men in the < 55-year age group is the probable greater difficulty experienced by women in quitting smoking. 18 - 20 This is probably related both to physical factors, such as the relationship between nicotine and female hormones, and to emotional factors associated with mood and affect. In addition, earlier age at smoking initiation and longer-term tobacco consumption translate into greater difficulty in quitting smoking.…”
Section: Discussionmentioning
confidence: 99%
“…This is inconsistent with previous findings that the majority of female smokers participating in smoking cessation programs were college graduates. 16 In previous studies, female smokers who had not completed college were shown to have a lower intention to quit smoking. 17 Therefore, it is encouraging that the participants in this study had indicated an intention to quit smoking and participate in the smoking cessation program despite a lower level of education.…”
Section: Discussionmentioning
confidence: 92%
“…The higher prevalence of users who sought treatment for MDI may be related to the characteristics of the study site, since this is an area of the city where the concentration of crack users is high (14) . Moreover, epidemiological studies show a significant increase in the consumption of this substance among women, even though such use continues to be more prevalent among men (9,15) .…”
Section: Discussionmentioning
confidence: 99%